2021
DOI: 10.3389/fgene.2021.705122
|View full text |Cite|
|
Sign up to set email alerts
|

RNA Polymerase III, Ageing and Longevity

Abstract: Transcription in eukaryotic cells is performed by three RNA polymerases. RNA polymerase I synthesises most rRNAs, whilst RNA polymerase II transcribes all mRNAs and many non-coding RNAs. The largest of the three polymerases is RNA polymerase III (Pol III) which transcribes a variety of short non-coding RNAs including tRNAs and the 5S rRNA, in addition to other small RNAs such as snRNAs, snoRNAs, SINEs, 7SL RNA, Y RNA, and U6 spilceosomal RNA. Pol III-mediated transcription is highly dynamic and regulated in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 91 publications
0
12
0
2
Order By: Relevance
“…The RNA polymerase III is now considered linked to aging and longevity through its action on TORC and insulin genes as well as its activity on genes related to telomerase activity. 51, 52 However, we have shown only an immediate effect on the chromatin complexes related to H3K4me3, as well as an absence of long-term effect on polr3d mRNA. The miR-320-3p has been studied for post-transcriptional gene silencing in the cytoplasm of rat endothelial and cardiac cell cultures derived from diabetes situations, on several genes among which the heat shock protein family B (small) member 6 .…”
Section: Discussionmentioning
confidence: 69%
“…The RNA polymerase III is now considered linked to aging and longevity through its action on TORC and insulin genes as well as its activity on genes related to telomerase activity. 51, 52 However, we have shown only an immediate effect on the chromatin complexes related to H3K4me3, as well as an absence of long-term effect on polr3d mRNA. The miR-320-3p has been studied for post-transcriptional gene silencing in the cytoplasm of rat endothelial and cardiac cell cultures derived from diabetes situations, on several genes among which the heat shock protein family B (small) member 6 .…”
Section: Discussionmentioning
confidence: 69%
“…Both TOR signalling and RNA Polymerase III are important regulators of anabolic processes, and control an wide array of cellular functions including reproduction and lifespan 16 . Here we show that TOR and Pol III interact in a time dependent manner, and that knockdown of each component individually, sequentially or in parallel influences the outcome of both reproductive and longevity processes (Fig.…”
Section: Rna Polymerase III and Tor Signalling Interact Temporally To...mentioning
confidence: 99%
“…Other Pol III transcripts include small nuclear (snRNAs) and small nucleolar (snoRNAs) both of which are implicated in RNA processing, the 7SK snRNAs that plays role in regulating transcription, as well as other small RNAs including Y RNA, L RNA, vault RNA and U6 spliceosomal RNA 3,4 Pol III-mediated transcription regulates a wide range of biological processes including cell and organismal growth [5][6][7][8] , the cell cycle 9 , differentiation 8,10,11 , development 12 , regeneration 13 and cellular responses to stress 14 . Pol III subunits have also been implicated in a wide variety of disease states and lifespan [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Pol III general transcription factors, oncogenic factor (c-MYC), tumour suppressor (p53) and signalling transduction factors (JNK and PTEN/AKT) can also tightly modulate Pol III – mediated transcription ( Gomez-Roman et al, 2003; Crighton et al, 2003; Sriskanthadevan-Pirahas et al, 2018; Zhong and Johnson, 2009; Woiwode et al, 2008 ). MAF1, a well-characterized factor repressing Pol III-directed transcription ( Kulaberoglu et al, 2021; Bonhoure et al, 2020 ), has recently been shown to regulate osteoblast differentiation and bone mass formation ( Phillips et al, 2022 ); and this factor has also been confirmed to improve cardiac hypertrophy and inhibit the synthesis of Pol III products by interacting with ERK ( Sun et al, 2019 ). It has been reported that tRNA (tRNA) biogenesis and specific tRNAs such as tRNA Leu -CAA and tRNA Tyr -GTA are required for the regulation of senescence ( Guillon et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%